2022
DOI: 10.3340/jkns.2021.0275
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Stents-Assisted Coiling for Vertebral Artery Dissecting Aneurysm : LVIS Stent within Neuroform EZ Stent

Abstract: Objective : To evaluate the safety and efficacy of an overlapped stenting-assisted coiling technique in treating vertebral artery dissecting aneurysm (VADA) via Low-profile Visualized Intraluminal Support (LVIS) stent-within-Neuroform EZ stent.Methods : From January 2017 to June 2019, 18 consecutive patients with VADAs (ruptured : unruptured=5 : 13) were treated with the overlapping stents assisted-coiling technique in our center. The overlapping manner was a Neuroform EZ stent being deployed first, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Liu et al found that using multiple overlapping stents resulted in a 77.8% immediate successful embolization rate. At 21.3 months post-operation, 94.4% of patients achieved an mRS score of 0-2 [24]. Our study yielded similar results, with an immediate embolization success rate of 85.2%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Liu et al found that using multiple overlapping stents resulted in a 77.8% immediate successful embolization rate. At 21.3 months post-operation, 94.4% of patients achieved an mRS score of 0-2 [24]. Our study yielded similar results, with an immediate embolization success rate of 85.2%.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, the use of overlapping stents has been explored for treating PCDAs, demonstrating favorable conditions for enhancing blood thrombosis [24][25][26]. To the best of our knowledge, there are limited studies on treating PCDAs using overlapping stents in acute hemorrhagic scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated the effectiveness and safety of treatments that involve placing a different type of closed-cell stent within an open-cell stent, with the expectation of additional effects. 6 In conclusion, visualizing the degree of stent deployment during retreatment in SAC has been challenging. However, using a balloon for stent visualization may provide a solution to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated the effectiveness and safety of treatments that involve placing a different type of closed-cell stent within an open-cell stent, with the expectation of additional effects. 6 …”
Section: Discussionmentioning
confidence: 99%
“…However, as previously demonstrated in previous study and through our own experience, using two LVIS stents can lead to stent migration when passing the microcatheter to deploy the second stent, and they may not overlap in the desired position. Furthermore, the elevated metal coverage rate increases the risk of ischemic complications 19) .…”
Section: Discussionmentioning
confidence: 99%